Akurasi Arah Kiblat Pemakaman Desa Ponteh Kecamatan Galis Kabupaten Pamekasan - Hosen .; Eka Nurhalisa (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2019)
The Cemetery conditions in Ponteh Village, Galis Sub district, Pamekasan Regency do not appear in line and seem messy both from the shaf rows and the kiblah direction of the  cemetery. In this article there are two main issues that are the focus of the problem. First, how is the method of determining the burial Kiblah direction at the Cemetery of Ponteh Village, Galis District, Pamekasan Regency. And second, how is the accuracy of the burial Kiblah direction in the Cemetery of Ponteh Village, Galis District, Pamekasan Regency. The location of this study is in three cemeteries in Ponteh Village, Galis District. The method used is qualitative phenomenological approach in the form of descriptive analysis. Research data obtained from interviews, observations and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results show; (1) The method used by the community in determining the cemetery kiblah direction is by estimating and beliefs based solely on feelings called the taqribī method by facing westward and then slightly tilted to the north. There is also an excavation of the burial ground following the direction of the cemetery location and the position of the burial ground located next to it. Second, according to the calculation result of Islamic astronomy, the direction of the cemetery Ajih 66º 9 '53.7 "(N-W), the Cemetery of Bângger 66º 9' 50.87" (N-W), and the Cemetery of Kaèl 66º 9 '48.93 "(N –W). The accuracy analysis result of the Kiblah direction of each cemetery which samples are 50 tombs in groups obtained was the cemetery that using data according to the calculation of Kiblah, for Ajih Cemetery 3 graves (6%), Bânger's cemetery 6 graves (12%) and Kaèl zero graveyard (0% ). Less to the north of 1 ° -5 °, the Ajih cemetery 14 graves (28%), Bânger cemetery are 26 graves (52%) and Kaèl cemetery are 11 graves (22%). Less to the south 1 ° -5 ° less to the south, Ajih Cemetery 2 graves (4%), the Bârger Cemetery 3 graves (6%) and the Kaèl cemetery is nil (0%). Deviation of 6 ° -10 ° less to the north, Ajih cemetery is zero graveyard (0%), Bânger Cemetery are 3 graves (6%) and Kaèl cemetery is zero (0%). Deviations from 6 ° -10 ° to the south, for Ajih Cemetery 30 graves (60%), the Bânger cemetery are 11 graves (22%) and the Kaèl cemetery  are 14 graves (28%). And those which stray northward 10 ° and above are not found in all the camps. However, the deviation of the Kiblah direction of more than 10 ° to the south was found in the Ajih cemetery and Bânger cemetery, each with 1 grave (2%), and the Kaèl cemetery 25 graves (50%)